1961
DOI: 10.1063/1.1728359
|View full text |Cite|
|
Sign up to set email alerts
|

Growth from the Melt. III. Dendritic Growth

Abstract: A mathematical treatment of steady-state dendritic growth from pure and alloy liquids has been developed for isothermal and nonisothermal dendrites. The velocity of dendritic growth, dendrite size, dendrite direction, and the alloy content of the dendrite have been calculated as a function of the bath supercooling, the alloy content of the bulk liquid, and the atomic kinetics of the material. To specify the problem completely it was necessary to choose some ``optimization'' condition. We have chosen the condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(45 citation statements)
references
References 17 publications
0
45
0
Order By: Relevance
“…Although the B-F and C-K models assume the uniform distribution of solute elements in liquid phase, Doherty et al, 21) Weinberg et al 27) and Sugiyama et al 30) suggested that during the initial solidification stage near the mold side, the diffusion layer exists ahead of solid-liquid interface and, hence, the effective partition coefficient increases with the cooling rate according to Bolling-Tiller model. 31) Their suggestion results in the less microsegregation in the mold side compared with the center part of the ingot. In addition, other explanations were proposed for the increase in the microsegregation from the mold side to the center.…”
Section: )mentioning
confidence: 99%
“…Although the B-F and C-K models assume the uniform distribution of solute elements in liquid phase, Doherty et al, 21) Weinberg et al 27) and Sugiyama et al 30) suggested that during the initial solidification stage near the mold side, the diffusion layer exists ahead of solid-liquid interface and, hence, the effective partition coefficient increases with the cooling rate according to Bolling-Tiller model. 31) Their suggestion results in the less microsegregation in the mold side compared with the center part of the ingot. In addition, other explanations were proposed for the increase in the microsegregation from the mold side to the center.…”
Section: )mentioning
confidence: 99%
“…Moreover, application of capillarity as the temperature boundary condition on the solid-liquid interface comprises the identical methodology used since the earliest models of dendritic growth were considered over 50 years ago. [7,8] In the next section, we show that the Gibbs-Thomson capillarity effect is much more than just a boundary condition on the surrounding transport field. Capillarity introduces temperature gradients along a dendritic interface-albeit extremely weak ones-so that the GibbsThomson equilibrium temperature distribution acts as an independent energy field during crystal growth, producing, as we shall demonstrate, more important effects on the branching process than recognized previously.…”
Section: E Testing Current Theories Of Dendritic Growthmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] These efforts included precepts and hypotheses on dendritic interfacial physics as varied as the following: Take, for example, item (a), the concept of maximum velocity, which would occur, hypothetically, for a paraboloidal dendrite, the solid-liquid interface of which has interfacial energy, i.e., capillarity. As all interfaces have excess free energy, or surface tension, this idea could, conceivably, have provided a reasonable supposition about the operating state of dendrites: namely, that dendrites grow steadily when they achieve their maximum velocity, as allowed by the thermal conduction field and the level of supercooling specified in the melt.…”
Section: Interfacial Physicsmentioning
confidence: 99%
“…It was pointed out that due to the interfacial curvature and interfacial kinetics, the interface is essentially nonisoconcentrational for an isothermal transformation 3,4 and nonisothermal in solidification. 5,6 Approximate treatments were presented therein.…”
Section: Introductionmentioning
confidence: 99%